The Effect of Work Environment, Workload, and Work Engagement on Employee Performance with Work Commitment as mediation and Generation Z as Control Variable in Batam City - Muhammad Donal Mon; Jane Evelin Susilo; Antony Sentoso (Cita Konsultindo Research Center, 2023)
This research aims to determine the influence of work environment, workload, and work engagement on employee performance with work commitment as a mediation for generation Z. This research uses descriptive quantitative methods and 400 respondents, with generation Z as the population. SMART PLS were used as the data processing technique. The results of the analysis from this research shows that environment, workload, and work engagement have a significant positive influence on performance with work commitment as a mediation for generation Z in Batam. The usage of gender as control variables in this research is unique/different and the result shows that gender does not have a significant influence on the performance of generation Z.